Constituents, pharmacological activities, pharmacokinetic studies, clinical applications, and safety profile on the classical prescription Kaixinsan - Chen, Liping; Jiang, Lin; Shi, Xiaoyu; Yang, Jihong; Wang, Rong; Li, Wenbin (Frontiers in Pharmacology, 2024)
Kaixinsan (KXS) is a noteworthy classical prescription, which consists of four Chinese medicinal herbs, namely Polygalae Radix, Ginseng Radix et Rhizoma, Poria, and Acori Tatarinowii Rhizoma. KXS was initially documented in the Chinese ancient book Beiji Qianjin Yaofang written by Sun Simiao of the Tang Dynasty in 652 A.D. As a traditional Chinese medicine (TCM) prescription, it functions to nourish the heart and replenish Qi, calm the heart tranquilize the mind, and excrete dampness. Originally used to treat amnesia, it is now also effective in memory decline and applied to depression. Although there remains an abundance of literature investigating KXS from multiple aspects, few reviews summarize the features and research, which impedes better exploration and exploitation of KXS. This article intends to comprehensively analyze and summarize up-to-date information concerning the chemical constituents, pharmacology, pharmacokinetics, clinical applications, and safety of KXS based on the scientific literature, as well as to examine possible scientific gaps in current research and tackle issues in the next step. The chemical constituents of KXS primarily consist of saponins, xanthones, oligosaccharide esters, triterpenoids, volatile oils, and flavonoids. Of these, saponins are the predominant active ingredients, and increasing evidence has indicated that they exert therapeutic properties against mental disease. Pharmacokinetic research has illustrated that the crucial exposed substances in rat plasma after KXS administration are ginsenoside Re (GRe), ginsenoside Rb1 (GRb1), and polygalaxanthone III (POL). This article provides additional descriptions of the safety. In this review, current issues are highlighted to guide further comprehensive research of KXS and other classical prescriptions.